Clinico-epidemiological study of dengue fever in Ajmer region - Rawat, Dharmendra; Singh, Kanwar; Garg, Pukhraj (International Journal of Contemporary Pediatrics, 2019)
Background: Dengue infection is a major challenge to public health, especially in South-East Asia. It present with a diverse clinical spectrum. Estimates suggest that annually over 50 million cases of dengue hemorrhagic fever (DHF) occur in Asian countries with a case fatality rate of less than 5%. Of those with DHF, at least 90% are children younger than 15 years old. In humans, dengue infection causes a spectrum of illness ranging from relatively mild, non-specific viral syndrome known as Dengue fever (DF) to severe hemorrhagic disease and death. Definitive early Dengue diagnosis requires laboratory tests and those suitable for use at this stage of illness are either costly, such as RT-PCR for Dengue; not sufficiently rapid, such as virus isolation. Currently test available are NS1 antigen detection and ELISA for dengue, IgM and IgG antibodies. Objective of this study is to study clinico-epidemiological and haematological features of Dengue infection. Methods: Prospective observational study involving initial 100 registered cases who were serologically confirmed dengue infection for a period of one year. Results: DF, DHF and DSS were found in 41%, 53% and 6% patients respectively. Most common presenting complaint and bleeding manifestation were fever and petechiae. Uncommonly altered sensorium and icterus were found in severe dengue infection. 6% patients had coagulopathy, 37 patients had hepatic involvement and 2 patients had deranged renal function who had DSS. Fever was present in (100%) cases of DF, DHF and DSS. 26% patients had their platelet count <50000/mm3. Conclusions: Dengue is a common disease in the India with wide spectrum of clinical presentations, affecting 5-15 years age group children commonly. It is one of the dreaded fevers but early diagnosis and management according to recent WHO guidelines can decrease case fatality rate significantly.